2011
DOI: 10.1093/geront/gnr035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Participation in TimeSlips, a Creative Group-Based Storytelling Program, on Medical Student Attitudes Toward Persons With Dementia: A Qualitative Study

Abstract: This is the first known pilot study to suggest that participation in a creative group-based storytelling program might improve medical student attitudes toward persons with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…Other programs described a variable number of learning activities over time and included some preparatory theory elements using traditional lecture / tutorial format followed by practice based experience (George et al, 2013;Jefferson et al 2012;George et al, 2011;Jordan and Church, 2013). They describe a story telling program, where students met with a group of people with dementia (up to 10), in the community, on four occasions for up to 90 minutes.…”
Section: Educational Content and Teaching And Learning Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other programs described a variable number of learning activities over time and included some preparatory theory elements using traditional lecture / tutorial format followed by practice based experience (George et al, 2013;Jefferson et al 2012;George et al, 2011;Jordan and Church, 2013). They describe a story telling program, where students met with a group of people with dementia (up to 10), in the community, on four occasions for up to 90 minutes.…”
Section: Educational Content and Teaching And Learning Methodsmentioning
confidence: 99%
“…However some interventions were more specific and indicated that they were designed to improve participants' knowledge or understanding of dementia (Jefferson et al, 2012;Paquette et al, 2010). Ross (2012) on the other A number of studies specifically focused on training aimed to improve students' perceptions and attitudes to people with dementia (George et al, 2013;George et al, 2011;Kaf et al, 2011), with one aiming to introduce students to career opportunities in working with older people (Jefferson et al 2012). In relation to meeting the psychosocial needs of people with dementia, Jordan and Church Although all the studies inherently addressed communication skills by the nature of the learning activities, only one study specifically described aims to improve students' communication skills in working with people with dementia (Jefferson et al 2012).…”
Section: Aims Of the Education / Training Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results include improved levels of expression, better communication in AD patients [19], and increased medical student interaction [22] with improved medical students' attitudes towards people with dementia when they were included in the sessions with patients [23]. Furthermore, Timeslips has been shown to improve caregivers' attitudes toward dementia patients because it has improved the overall relationship between staff and residents [24].…”
Section: Timeslipsmentioning
confidence: 99%